High-Rate Mechanical Properties of Energetic Materials - Walley, S; Siviour, C; Drodge, DR; Williamson, D (2010)
Compared to the many thousands of studies that have been performed on the energy release mechanisms of high energy materials, relatively few studies have been performed (a few hundred) into their mechanical properties. Since it is increasingly desired to model the high rate deformation of such materials, it is of great importance to gather data on their response so that predictive constitutive models can be constructed. This paper reviews the state of the art concerning what is known about the mechanical response of high energy materials. Examples of such materials are polymer bonded explosives (used in munitions), propellants (used to propel rockets), and pyrotechnics (used to initiate munitions and also in flares). © 2010 TMS.